American wife a novel - Sittenfeld, Curtis 1975- (Random House, 2009)
On what might become one of the most significant days in her husband's presidency, Alice Blackwell considers the strange and unlikely path that has led her to the White House--and the repercussions of a life lived, as she puts it, "almost in opposition to itself." How can she both love and fundamentally disagree with her husband? How complicit has she been in the trajectory of her own life? What should she do when her private beliefs run against her public persona?--From publisher description.